Influence of surface topografy! on zig-zag defects in ferroelectric liquid crystal displays - Pirš, Janez (Informacije MIDEM, 1998)
The influence of surface conditions on chevron structures and zig-zag defects in a SmC liquid crystall cell is studied both experimentally and theoretically. In order to gain insight into basic properties of the system the Landau-Ginzburg type theory is used in terms of the nematic director field and the smectic complex order parameter. On a simple model system transitions in the C1 and C2 chevron structures are studied as functions of the surface pretilt angle. The threshold conditions are calculated. The width of the straight element of the domain wall (running parallel to smectic layers) and the costs for its formation are estimated. In the experimental part of the work the effect of the confining substrate with controlled variation of the surface slope on the formation of zig-zag defects is analysed. Observed results are in line with theoretical expectations
Keywords: lastnosti; samarijev karbid; ševronska struktura; tekoči kristali